Cloning of the HLA class II region in yeast artificial chromosomes. - Ragoussis, J (1991)
Yeast artificial chromosomes (YACs) have been applied to clone the entire class II region of the human major histocompatibility complex (MHC), including its flanking regions, in a contig over 1.5 million base pairs (bp) long. The human DNA inserts in the YACs have a size between 60 and 1300 kbp and were isolated from two EcoRI partial digest libraries. The gaps between DRA and DRB, DRB and DQA, and DOB and DPA, which had not been cloned by other means, have been bridged with YAC clones. The contig extends through the 400 kpb of DNA between the DRA and C4 genes, thus linking the class II region with the complement gene cluster in the class III region. The cloning in YACs has been supported by a conventional cosmid walk of 290 kbp in the C4-DRA region. Restriction enzyme sites in the YAC clones were compared to the sites in the cosmid walk, to published cosmid clones, and to the already existing physical maps, leading to a detailed characterization of a region of the human genome over 1500 kbp. The YAC clones will be valuable for functional analysis of the MHC.